Scope of Additive Manufacturing in Pakistani construction Industry: Exploring challenges - Rauf, Fatima (2021)
Additive manufacturing technology has become a new innovative method of production and construction for the past one decade. This technology, also known as 3DP is being used in multiple industries Like automotive, aerospace, electronics, and pharmaceutical. Seeing the AMs progress in these industries, much work has also been done in developed countries, construction sector in applying AM technology by using Aggregate based, polymer and metallic materials. Early research suggests that additive manufacturing technology used in the construction industry is able to lessen labor costs, decrease waste material as well as construct customized complex geometrical structure that can be hard accomplish through traditional construction methods. Various challenges, on the other hand, can hinder and slow the adoption of AM. In various cases, challenges like size limitations, imperfection in appearance, cost, on-site and of-site fabrication , mass manufacturing, material heterogeneity and structural reliability and AM standardisation and intellectual property have been identified in the literature. This study examines literature, on the scope and challenges of AM in technologically advanced countries. It uses four case-based evidence to underline the benefits and status of AM in accelerating the R&D in emerging economies, specifically to Pakistan. Furthermore, it supports in identifying the external and internal challenges faced by companies belonging to the Pakistani construction industry, regarding the adoption of AM technologies in Pakistan to limelight.